Prognostic awareness in advanced cancer patients and their caregivers: A longitudinal cohort study - Loučka, Martin; Vlčková, Karolína; Tučková, Anna; Poláková, Kristýna; Houska, Adam; Matějů, Martin; Donátová, Zuzana (Psycho-oncology, 2021)
OBJECTIVE: The aim of this study was to analyse longitudinal development of prognostic awareness in advanced cancer patients and their families. METHODS: This was a longitudinal cohort study, involving 134 adult cancer patients, 91 primary family caregivers and 21 treating oncologists. Key eligibility criterion for patients was life expectancy less than 1 year (estimated by their oncologists using the 12-month surprised question). Structured interviews, including tools to measure prognostic awareness, health information needs, and demographics were conducted face to face or via phone three times over 9 months. Forty-four patients completed all three phases of data collection. RESULTS: Only 16% of patients reported accurate prognostic awareness, 58% being partially aware. Prognostic awareness of both patients and family caregivers remained stable over the course of the study, with only small non-significant changes. Gender, education, type of cancer, spirituality or health information needs were not associated with the level of prognostic awareness. Family caregivers reported more accurate prognostic awareness, which was not associated with patients' own prognostic awareness (agreement rate 59%, weighted kappa 0.348, CI = 0.185-0.510). CONCLUSIONS: Prognostic awareness appears to be a stable concept over the course of the illness. Clinicians must focus on the initial patients' understanding of the disease and be able to communicate the prognostic information effectively from the early stages of patients' trajectory.
Keywords: prognóza; Prognosis; Longitudinal Studies; osoby pečující o pacienty; nádory; kohortové studie; lidé; longitudinální studie; Neoplasms; Humans; Cohort Studies; Caregivers